Manhattan dreaming - Heiss, Anita, 1968- (North Sydney, N.S.W. : Bantam, 2010)
"Lauren is a curator at the National Aboriginal Gallery in Canberra. She's good at her job, passionate about the Arts, and takes work seriously. It's easy for Lauren to focus on work, that is, when she's not focussing on Adam. Lauren is smitten with, or as her friends say, obsessed with Adam - the halfback for the Canberra Cockatoos.But Adam is a player, on and off the field. Lauren knows he's the one, but he doesn't seem to feel the same way about her. If she just waits long enough, though, surely he'll realise how much he needs her?Then her boss offers her the chance of a lifetime - a fellowship at the Smithsonian in New York. Lauren has to make some big decisions: The Man or Manhattan?"
Keywords: Literature and stories - Fiction; Canberra (ACT SI55-16)